Is social isolation during the COVID-19 pandemic a risk factor for depression? - Adaene Alves Machado de Moura; Igor Roberto Bassoli; Belisa Vieira da Silveira; Alessandra Diehl; Manoel Antônio dos Santos; Ronildo Alves dos Santos; Christopher Wagstaff; Sandra Cristina Pillon (Associação Brasileira de Enfermagem, 2022)
ABSTRACT Objective: To assess factors associated with depression among higher education students and professionals during the peak of the COVID-19 pandemic. Method: quantitative study with a cross-sectional design. 550 students and professionals participated. The data were collected by means of a digital questionnaire that included Patient Health Questionnaire-9 to assess depressive symptoms. Results: The factors related to depression and social isolation outcomes were significantly associated with the female gender (n= 149; 37,8%; Odds Ratio OR=2,0), white (n=127; 37,2%; OR=1,60), young people (n=130; 39,4%; OR=2,0), without religion (n=70; 40,2%; OR=1,64), with financial problems (n=80; 53,0%; OR=2,40) and family problems (n=98; 47,3%; OR=1,77); who suffered violence during the quarantine (n=28; 58,3%; OR=2,33), increased the use of illicit drugs (n=16; 59,3%; OR=2,69), used sedatives without a medical prescription (n=75; 54,0%; OR=2,94), lived in conflicting relationships (n=33; 54,1%;OR=2,14), lost their job during the pandemic (n=32; 59,3%; OR=1,99) and presented symptoms of anxiety related to COVID-19 (n=155; 45,2%; OR=3,91). Conclusion: there is a meaningful relationship between vulnerability and adopting risk behaviors during the pandemic-imposed social isolation with depressive symptoms. We suggest that health professionals be attentive to the need to adjust their psychosocial interventions when promoting strategies when promoting strategies to mitigate the effects and risks to mental health.